Multi-scale analysis method for composite-metal hybrid truss nodes using the MPC-submodel approach - Lu, Huadong; Li, Fei; Zhao, Qilin; Hu, Hao; Zhou, Lijun; Zhou, Kuangyu (Structures (Oxford), 2023)
Large-scale composite material-metal composite structures subjected to multi-axial loading conditions experience stress concentration and damage due to the dissimilar mechanical properties of the materials. A multi-scale refined modeling analysis is essential for accurately investigating these hybrid truss nodes. However, the existing multi-scale analysis methods face certain challenges, including modeling difficulties, reduced computational efficiency, convergence issues, and inaccurate boundary conditions. In this study, we first proposed an MPC-submodel approach based on the submodeling method and the multi-point constraint (MPC) technique to address these challenges in multi-scale computations of large-scale structures. Subsequently, we conducted experimental tests on composite-metal hybrid trusses and performed finite element simulations on key nodes using the proposed method, validating its accuracy. Finally, we applied the proposed method to investigate the key nodes within a 200-m long-span composite-metal composite truss bridge. By comparing the results with those from finite element simulations using the multi-point constraint method, we effectively demonstrated the advantages of the proposed method. The results indicated that our approach accurately modeled boundary conditions, significantly reduced computational time, and improved efficiency while maintaining computational accuracy.